Influence of Surface Sputtering during High-Intensity, Hot Ion Implantation on Deep Alloying of Martensitic Stainless Steel; Metals; Vol. 13 - iss. 9 - Ryabchikov A. I. Aleksandr Ilyich; Korneva O. S. Olga Sergeevna; Ivanova A. I. Anna Ivanovna; Dektyarev S. V. Sergey Valentinovich; Vakhrushev D. O. Dimitry Olegovich; Gurulev A. V. Aleksandr Valerjevich (2023, 2023)
This article is devoted to the study of the effect of ion sputtering on the alloy surface, using the example of martensitic stainless steel AISI 420 with ultrahigh-dose, high-intensity nitrogen ion implantation on the efficiency of accumulation and transformation of the depth distribution of dopants. Some patterns of change in the depth of ion doping depending on the target temperature in the range from 400 to 650 ◦C, current density from 55 to 250 mA/cm2, and ion fluence up to 4.5 × 1021 ion/cm2 are studied. It has been experimentally established that a decrease in the ion sputtering coefficient of the surface due to a decrease in the energy of nitrogen ions from 1600 to 350 eV, while maintaining the ion current density, ion irradiation fluence and temperature mode of target irradiation increases the ion-doped layer depth by more than three times from 25 µm to 65 µm. The efficient diffusion coefficient at an ion doping depth of 65 µm is many times greater than the data obtained when stainless steel is nitrided with an ion flux with a current density of about 2 mA/cm2.